2023
DOI: 10.1002/cre2.731
|View full text |Cite
|
Sign up to set email alerts
|

Contour angle and peri‐implant tissue height: Two interrelated features of the implant supracrestal complex

Abstract: Objectives: Recent research has suggested the contour of the prosthesis and the vertical height of the peri-implant mucosa as important parameters that can influence the long term health and stability of the peri-implant tissue. In particular, overcontouring of the prosthesis has been correlated with an increased risk for peri-implantitis, while reduced soft tissue height has been associated with marginal bone loss, recession, and other soft tissue complications. Although these two parameters have been investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In particular, the association of the deep angle with mucosal width is something that has not been presented before. From a purely geometrical point of view, the peri‐implant mucosa appears to fill a pyramid shape, supplementary to the trapezoid shape of the implant prosthesis, when the prosthetic contour remains within 30°, as recommended by Puisys et al ( 2023 ). The deep angle has a critical importance for the marginal bone, as studies have shown increased marginal bone remodeling (Valente et al 2020 ) and early marginal bone loss when this angle exceeds 28°–34° (Han et al 2023 ).…”
Section: Discussionmentioning
confidence: 98%
“…In particular, the association of the deep angle with mucosal width is something that has not been presented before. From a purely geometrical point of view, the peri‐implant mucosa appears to fill a pyramid shape, supplementary to the trapezoid shape of the implant prosthesis, when the prosthetic contour remains within 30°, as recommended by Puisys et al ( 2023 ). The deep angle has a critical importance for the marginal bone, as studies have shown increased marginal bone remodeling (Valente et al 2020 ) and early marginal bone loss when this angle exceeds 28°–34° (Han et al 2023 ).…”
Section: Discussionmentioning
confidence: 98%